Analisis Peran Kepala Sekolah dalam Upaya Meningkatkan Mutu Pendidikan Manajemen Sekolah di SD Rumpun Muslim Jatisrono - Ghoffar, Muhammad Fathin Abdul; Murtadho, Imam; Khoir, Mulyanto Abdullah (TSAQOFAH, 2025)
This research analyzes the role of the principal in improving the quality of school management at the Rumpun Muslim Jatisrono Islamic Elementary School, Wonogiri Regency. Through qualitative descriptive methods, the research results show that school principals have a central role in aspects of leadership, decision making, supervision and development of teaching staff. The school principal functions as a director, motivator and supervisor, and ensures that the policies implemented are in line with the school's vision and mission. Challenges such as limited resources and dynamics of relationships between parties in schools can be overcome through a systematic approach that involves all school components. In addition, teacher professional development is an important element in improving the quality of learning. With effective leadership, the quality of school management can be improved, thereby having a positive impact on the overall quality of education.